Development of an in vehicle road user information interface - KOUGIOUMOUTZI, MARIA (My University, 2013)
In order to mitigate road accidents car manufacturers introduce in the market increasingly focused safety control systems, such as advanced driver assistance systems (ADAS). The current ADAS systems provide single stage warning features to alert the driver when the risk level rises over a certain amount. Theoretically if the drivers are mentally prepared, informed by advisory warnings prior to the collision warnings they are expected to respond better on a critical situation. Our aim is to enhance the driver’s situational awareness by providing continuously real time information about the road users under normal driving conditions and not only when a warning has occurred. Based on this idea, three stages are introduced according to the threat level: informative, advisory and warning. The user interface we are introducing is designed to be perceived in an intuitive and natural way, not as a distraction but as an assistance in comprehending the outside environment.
Keywords: Interaktionsteknik; Interaction Technologies